2020
DOI: 10.1111/aos.14351
|View full text |Cite
|
Sign up to set email alerts
|

Decreased retinal thickness in preschool offspring of maternal gestational hypertension: the Nanjing Eye Study

Abstract: PurposeTo evaluate the influence of maternal gestational hypertension (GH) on retinal thickness of 5–6‐year‐old children, including macular thickness, ganglion cell‐inner plexiform layer (GC‐IPL) thickness and peripapillary retinal nerve fibre layer (RNFL) thickness.MethodsAs part of Nanjing Eye Study, comprehensive ocular examinations were conducted in children aged 61–72 months, including noncycloplegic refraction, ocular biometric parameters and retinal parameters. Retinal thickness was measured by Spectral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
2
11
1
1
Order By: Relevance
“…The characteristics of the included studies 19–65 are summarised in Table 1. Data from a total of 33,559 subjects were extracted, of which 31,722 subjects came from population‐based studies.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included studies 19–65 are summarised in Table 1. Data from a total of 33,559 subjects were extracted, of which 31,722 subjects came from population‐based studies.…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive questionnaire was self-administered by legal guardians at baseline, including parental myopia, outdoor time and near activities time [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is not clear why differences in macula thickness exist between ethnic groups. Factors which impact retinal thickness measurements in children include birth weight, prematurity, maternal gestational hypertension, diabetes and smoking, and body mass index [21][22][23][24][25]. However, while these factors may explain some of the variation found in the current study, most have been shown to influence retinal thickness by less than < 6 μm [22][23][24][25] and are therefore unlikely to explain the larger difference found between Aboriginal and/or Torres Strait Islander children and non-Indigenous children in this study.…”
Section: Plos Onementioning
confidence: 58%